2016
DOI: 10.1016/j.clinph.2014.12.035
|View full text |Cite
|
Sign up to set email alerts
|

Visual evoked potentials in migraine: Is the “neurophysiological hallmark” concept still valid?

Abstract: Please cite this article as: Omland, P.M., Uglem, M., Hagen, K., Linde, M., Tronvik, E., Sand, T., Visual evoked potentials in migraine: Is the "neurophysiological hallmark" concept still valid ?, Clinical Neurophysiology (2015), doi: http://dx.doi.org/10. 1016/j.clinph.2014.12.035 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
62
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(70 citation statements)
references
References 67 publications
6
62
1
1
Order By: Relevance
“…Moreover, given this criticism, how can we still mention habituation defect as a neurophysiological hallmark of migraine? This is indeed the position expressed in the paper by Omland et al (2015) published in this issue of Clinical Neurophysiology. Here authors study habituation to VEP in normal subjects and in patients with migraine using visual stimuli of 16 0 size to complete the series of check sizes explored in previous studies (8 0 , 31 0 , 62 0 , 65 0 ).…”
Section: See Article Pages Xxx-xxxsupporting
confidence: 53%
See 3 more Smart Citations
“…Moreover, given this criticism, how can we still mention habituation defect as a neurophysiological hallmark of migraine? This is indeed the position expressed in the paper by Omland et al (2015) published in this issue of Clinical Neurophysiology. Here authors study habituation to VEP in normal subjects and in patients with migraine using visual stimuli of 16 0 size to complete the series of check sizes explored in previous studies (8 0 , 31 0 , 62 0 , 65 0 ).…”
Section: See Article Pages Xxx-xxxsupporting
confidence: 53%
“…Should we now consider instead the chance that lack of habituation would simply be the result of a methodological bias? From the evidence reported and reviewed by Omland et al (2015) and Sand (2014) it would seem so or at least that a serious criticism should be raised about. However, important caveats exist and deserve mention.…”
Section: See Article Pages Xxx-xxxmentioning
confidence: 99%
See 2 more Smart Citations
“…This finding is noteworthy for the long-standing debate about the variability of VEP habituation in migraine. While fluctuations over the migraine cycle likely account for intra-subject variability, there is no unanimously accepted explanation for the between-subject differences (8,9). It has been shown that stress is able to increase event-related potentials by decreasing habituation to a greater degree in migraine patients than in healthy subjects (10), and just before a migraine attack (11).…”
Section: Discussionmentioning
confidence: 99%